Chemical looping technology in CHP (combined heat and power) and CCHP (combined cooling heating and power) systems: A critical review - Rajabi, Mahsa; Mehrpooya, Mehdi; Haibo, Zhao; Huang, Zhen (Applied energy, 2019)
•Chemical looping combustion method is used to prevent CO2 emission.•Integration of chemical looping technology in CHP and CCHP systems is studied.•Structure of the processes integrated to chemical looping unit is discussed.•Layout of the integrated processes are classified and explained. Chemical looping combustion (CLC) as an oxy-fuel combustion method with no contact between air and fuel, is one methods that can be used for combustion to prevent CO2 emission in the atmosphere. Chemical looping reforming (CLR) and chemical looping hydrogen generation (CLHG) are procedures for hydrogen production with inherent CO2 separation. Chemical looping technology is also used in other systems such as gasification and air separation called chemical looping gasification (CLG) and chemical looping air separation (CLAS). This technology can play an important role in controlling air pollution, fuel consumption and clean fuel production which are main concerns of the last century in the world. In this paper, chemical looping technology used in multi-generation systems is reviewed and investigated. The processes with power, heating and cooling production, called CHP (combined heat and power) and CCHP (combined cooling heat and power) systems are elaborated. They are categorized by their main product and main units for benefit outputs. The main feature of this paper is to show the overall structure of the units and likewise the inputs and outputs of them for a better understanding and comparison. Also consumed fuels, applied oxygen carriers, main conditions in chemical looping units, chemical reactions and resulted efficiencies, are considered and discussed. The presented results can be very useful for awareness, comparison and decision making for future modeling or experimental studies. The results show that fuel cell-based systems yielded higher efficiencies about 60–70%. Also the highest electrical efficiency (67%) is related to the SOFC-based power generation processes.